1989
DOI: 10.1136/bjo.73.11.888
|View full text |Cite
|
Sign up to set email alerts
|

Eye injuries: a prospective survey of 5671 cases.

Abstract: SUMMARY 5671 patients with injuries presenting to a busy eye casualty department were examined prospectively to determine the incidence, aetiology, and severity of the injury. Of these cases 69-9% occurred at work, 18-3% during leisure and domestic activities (excluding recognised sport), 2-3% during sport, and 1-9% were due to assaults; contact lens injury occurred in a further 2-3%, and the cause was unknown in 5 3%. One hundred and two (1-8%) patients required admission to hospital, and of their injuries 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
99
4
11

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 20 publications
(1 reference statement)
22
99
4
11
Order By: Relevance
“…However, for final VA, it is thought to be related with accompanying anterior and posterior segment complications like traumatic cataract, glaucoma, iridodialysis vitreus hemorrhage, macular edema, and retinal detachment, as previously reported. [1,[19][20][21][22][23][24] The results of the current study were similar to those of previous studies conducted on traumatic hyphemas in adults with respect to the frequency of complications. [1,4,14,18,22] Increase in IOP is common in traumatic hyphema patients, especially in grades 3 and 4.…”
Section: Discussionsupporting
confidence: 81%
“…However, for final VA, it is thought to be related with accompanying anterior and posterior segment complications like traumatic cataract, glaucoma, iridodialysis vitreus hemorrhage, macular edema, and retinal detachment, as previously reported. [1,[19][20][21][22][23][24] The results of the current study were similar to those of previous studies conducted on traumatic hyphemas in adults with respect to the frequency of complications. [1,4,14,18,22] Increase in IOP is common in traumatic hyphema patients, especially in grades 3 and 4.…”
Section: Discussionsupporting
confidence: 81%
“…Also in the results we noticed an increase in the number of hyphema during holidays (including festival days and national holidays, 53.7%), the same with the results of Bouhaimed Manal et al [44], this is because of the large number of projectile toys sold to children during these days and the extra time of leisure.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies in the existing literature have shown that male patients formed the overwhelming majority of patients presenting with eye injuries, ranging from 70% to 87% of all ocular trauma. [6][7][8][9][10][11] Similar to the literature, 83% of the patients in the present study were male and the mean age was 34.16 years, and this corresponds to most other studies, which reported a mean age of about 30 years. [4,6,10,11] When we considered the setting of the injury, 72.1% of the patients had work-related injuries, and this result is similar to the preexisting literature.…”
Section: Discussionsupporting
confidence: 78%